Penerapan Teologi dalam Kebudayaan - Martin Elvis (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2018)
Theology should apply in the every area of ​​life, because we are all asked to be the doers of the Word. Values ​​in society are crystallized in the form of culture. But not all cultural values ​​that are formed have a good value. Are we going to be spectators and be passive and apathetic, or are we moved to apply theology in culture as a form of our contribution to express the truth of God's word that influences culture? What Abraham Kuyper has done in applying theology in culture can be an example for us. The authors carry out one of the application of theology in culture in everyday life, that is against the culture of Bajaj drivers who violate the traffic that resulted in two congregations died from being hit.